Modelling the erythroblastic island niche of dyserythropoietic anaemia type IV patients using induced pluripotent stem cells - May, Alisha; Ventura, Telma; Fidanza, Antonella; Volmer, Helena; Taylor, Helen; Romanò, Nicola; D’Souza, Sunita L.; Bieker, James J.; Forrester, Lesley M. (Frontiers in Cell and Developmental Biology, 2023)
Congenital dyserythropoietic anaemia (CDA) type IV has been associated with an amino acid substitution, Glu325Lys (E325K), in the transcription factor KLF1. These patients present with a range of symptoms, including the persistence of nucleated red blood cells (RBCs) in the peripheral blood which reflects the known role for KLF1 within the erythroid cell lineage. The final stages of RBCs maturation and enucleation take place within the erythroblastic island (EBI) niche in close association with EBI macrophages. It is not known whether the detrimental effects of the E325K mutation in KLF1 are restricted to the erythroid lineage or whether deficiencies in macrophages associated with their niche also contribute to the disease pathology. To address this question, we generated an in vitro model of the human EBI niche using induced pluripotent stem cells (iPSCs) derived from one CDA type IV patient as well as two iPSC lines genetically modified to express an KLF1-E325K-ERT2 protein that could be activated with 4OH-tamoxifen. The one patient iPSC line was compared to control lines from two healthy donors and the KLF1-E325K-ERT2 iPSC line to one inducible KLF1-ERT2 line generated from the same parental iPSCS. The CDA patient-derived iPSCs and iPSCs expressing the activated KLF1-E325K-ERT2 protein showed significant deficiencies in the production of erythroid cells with associated disruption of some known KLF1 target genes. Macrophages could be generated from all iPSC lines but when the E325K-ERT2 fusion protein was activated, we noted the generation of a slightly less mature macrophage population marked by CD93. A subtle trend in their reduced ability to support RBC enucleation was also associated with macrophages carrying the E325K-ERT2 transgene. Taken together these data support the notion that the clinically significant effects of the KLF1-E325K mutation are primarily associated with deficiencies in the erythroid lineage but it is possible that deficiencies in the niche might have the potential to exacerbate the condition. The strategy we describe provides a powerful approach to assess the effects of other mutations in KLF1 as well as other factors associated with the EBI niche.